1975
DOI: 10.1007/bf00687537
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the human spinal ganglia in varicella-zoster virus infection

Abstract: Spinal ganglia from a patient who died on the 6th day of varicella infection were examined by immunofluorescence and electron microscopy, and were compared with spinal ganglia from a patient dying on the 17th day of herpes zoster infection. In herpes zoster, typical intranuclear inclusion bodies were found in neurons, satellite cells and fibroblast-like cells of the ganglia, which contained numerous naked virus particles. In varicella, few changes were found by light microscopy but viral antigen was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Some cases also showed vascular involvement with perivascular lymphocytic cuffing and thrombosis noted (28,31). Similar features were noted in ganglia from the current study, particularly in the reactivated ganglia of HZ1, where focal necrosis was apparent.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some cases also showed vascular involvement with perivascular lymphocytic cuffing and thrombosis noted (28,31). Similar features were noted in ganglia from the current study, particularly in the reactivated ganglia of HZ1, where focal necrosis was apparent.…”
Section: Discussionsupporting
confidence: 83%
“…Previous histological studies of ganglia from patients with herpes zoster close to the time of death noted necrosis in part or the whole of the ganglia, with some hemorrhage and lymphocytic infiltration (27)(28)(29)(30)(31)(32). Some cases also showed vascular involvement with perivascular lymphocytic cuffing and thrombosis noted (28,31).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, a review of the literature revealed only 7 publications that have reported any such examination over the past 100-plus years, and those studies were restricted to basic histological observations (14,18,27,47,52,69,70). Our study provides the first detailed characterization of the repertoire of FIG.…”
Section: Discussionmentioning
confidence: 97%
“…As complex as the analysis of HSV latency in human ganglia has been, studies of the cellular distribution of latent VZV DNA in human ganglia have been even more so, despite numerous attempts using ISH (12,21,25,27,31), in situ PCR (17,27), immunohistochemical staining (8,26,32,36), and PCR of dissociated ganglion cells (28,30). There had long remained controversy, for example, as to which cells primarily harbor latent VZV.…”
mentioning
confidence: 99%